Cosmic Ray Mass Measurements with LOFAR - Buitink, Stijn; Bonardi, Antonio; Corstanje, Arthur; Enriquez, J. Emilio; Falcke, Heino; Hörandel, Jörg R.; Mitra, Pragati; Mulrey, Katie; Nelles, Anna; Rachen, Jörg Paul; Rossetto, Laura; Schellart, Pim; et al. (EPJ Web of Conferences, 2017)
In the dense core of LOFAR individual air showers are detected by hundreds of dipole antennas simultaneously. We reconstruct Xmax by using a hybrid technique that combines a two-dimensional fit of the radio profile to CoREAS simulations and a one-dimensional fit of the particle density distribution. For high-quality detections, the statistical uncertainty on Xmax is smaller than 20 g/cm2. We present results of cosmic-ray mass analysis in the energy regime of 1017 - 1017.5 eV. This range is of particular interest as it may harbor the transition from a Galactic to an extragalactic origin of cosmic rays.
CRIS-Team Scopus Importer:2023-08-15